1997
DOI: 10.1103/physrevb.55.6211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crack tip geometry on dislocation emission and cleavage: A possible path to enhanced ductility

Abstract: We present a systematic study of the effect of crack blunting on subsequent crack propagation and dislocation emission. We show that the stress intensity factor required to propagate the crack is increased as the crack is blunted by up to thirteen atomic layers, but only by a relatively modest amount for a crack with a sharp 60 • corner. The effect of the blunting is far less than would be expected from a smoothly blunted crack; the sharp corners preserve the stress concentration, reducing the effect of the bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
5
22
0
Order By: Relevance
“…In most cases sharp crack has been considered to begin with. Schiøtz et al (1996Schiøtz et al ( , 1997 and Fischer and Beltz (2001) have reported the effects of crack tip radius on the brittle and ductile crack growth and extension. Recently, Hampton and Nelson (2003) have characterized the SCG through thin sheets in terms of CTOA and the results have been applied to predict the crack tearing and instability in pressurized cylinder of the same thickness.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In most cases sharp crack has been considered to begin with. Schiøtz et al (1996Schiøtz et al ( , 1997 and Fischer and Beltz (2001) have reported the effects of crack tip radius on the brittle and ductile crack growth and extension. Recently, Hampton and Nelson (2003) have characterized the SCG through thin sheets in terms of CTOA and the results have been applied to predict the crack tearing and instability in pressurized cylinder of the same thickness.…”
Section: Introductionmentioning
confidence: 98%
“…They have used the elasticity solutions to solve for the thresholds to emit a fully formed dislocation on a slip plane intersecting the crack tip. The reduction of sharpness at the crack tip by providing a radius or blunting of crack tip increases the force required to propagate it (Schiøtz et al, 1996(Schiøtz et al, , 1997. Some conditions have been stipulated to predict whether a sharp crack tip will blunt leading to a ductile fracture, or continue to cleave in a brittle fashion (Fischer and Beltz, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The dislocations shield the stress field of the crack and may prevent further crack propagation. 2,3 The competing processes are commonly characterized in terms of G c , the critical release energy rate for cleavage, and in terms of G d , the critical energy release rate for dislocation emission: the process with the lower release energy rate is supposed to dominate. While cleavage at an atomistic level can be conveniently described within Griffith theory in combination with ab initio calculations, 4-7 the modeling of the dislocation emission is much more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Fully atomistic treatments by means of molecular dynamics ͑MD͒ and Monte Carlo ͑MC͒ have been applied to isolated defects in solids since the late 1960s. [1][2][3][4][5] The fairly recent advent of parallel computing, to which molecular simulation is ideally suited, has permitted multi-million-atom MD studies of the behavior of defective crystals. In particular, investigations by researchers at the Louisiana State University [6][7][8] and at IBM 9,10 have revealed valuable insight into atomic mechanisms of microcracking in silicon.…”
Section: Introductionmentioning
confidence: 99%